Study of the Efficiency of a Commercial Medical Organization Based on the Analysis of Economic Indicators - Shamilevna Idrisova, Maryam (2021)
Nowadays modern medical commercial organizations in Russia carry out a paid reception of the residents for the provision of paid medical services. The demand for such services has increased significantly today due to the heavy workload of state medical institutions. However, today consumers choose the most high-quality services in the medical field, so the economic activity of medical commercial companies directly depends on the extent where specialists can provide patients with an individual approach and high-quality treatment. The purpose of the work is to study the efficiency of a commercial organization based on the analysis of its financial documentation. The author comes to the conclusion that the medical organization "Medicon+" LLC has significantly improved its financial performance during the analyzed period. This indicates that the level of services provided, as well as their demand by the citizens, is constantly growing. The increase in the number of patient visits to specialists of the analyzed clinic is also caused by the increase in the incidence of the population due to the pandemic and the decrease in the capacity of public medical institutions in this regard. However, according to the analysis, it should be concluded that in the future, taking into account the quality of services provided and recognition, the clinic of LLC "Medicon+" will be able to function effectively even after the stabilization of the epidemiological situation in the country and in the world.